2008
DOI: 10.1007/s00330-008-1071-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement patterns in myotilinopathy and desminopathy detected by a novel neuromuscular whole-body MRI protocol

Abstract: Whole-body MRI (WB-MRI) has been successfully applied for oncologic and cardiovascular diagnostics, whereas imaging in myopathies usually employs dedicated protocols restricted to areas of specific interest. In this study, we propose a comprehensive neuromuscular WB-MRI protocol. Eighteen patients with degenerative and inflammatory muscle diseases were included. Whole-body imaging was performed on a 1.5-T MR system using parallel imaging. Examination time was 41:26 min. Coronal and axial T1-weighted and corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
(48 reference statements)
2
33
1
2
Order By: Relevance
“…The authors concluded that 1.5T is the preferred modality for WB MRI (Schmidt et al 2007). In accordance, two 3T muscular WB MRI studies (Kesper et al 2009;Kornblum et al 2006) showed subjectively inferior image quality and more artifacts in comparison to an own study at 1.5T (Schramm et al 2008). On the other hand, scan time at 3T can be reduced at a constant image quality and further technical innovations will improve 3T WB imaging.…”
mentioning
confidence: 50%
See 4 more Smart Citations
“…The authors concluded that 1.5T is the preferred modality for WB MRI (Schmidt et al 2007). In accordance, two 3T muscular WB MRI studies (Kesper et al 2009;Kornblum et al 2006) showed subjectively inferior image quality and more artifacts in comparison to an own study at 1.5T (Schramm et al 2008). On the other hand, scan time at 3T can be reduced at a constant image quality and further technical innovations will improve 3T WB imaging.…”
mentioning
confidence: 50%
“…In one of our WB MRI studies including 18 patients with different degenerative and inflammatory myopathies we found an involvement of the erector spinae muscles in 61.1 % (Schramm et al 2008). Affection of the erector spinae muscles seems also to be common in patients with myotonic dystrophy type 1 and 2 as described by Kornblum et al in their WB MRI study (Kornblum et al 2006).…”
mentioning
confidence: 67%
See 3 more Smart Citations